2022
DOI: 10.1007/s13201-022-01651-1
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of groundwater vulnerability methods in a porous aquifer in Greece

Abstract: Groundwater vulnerability assessment is critical for the effective groundwater management, particularly in areas with significant anthropogenic activities, such as agriculture. In this study, seven different methods, namely, DRASTIC, Pesticide DRASTIC, SINTACS, Nitrate SINTACS, GOD, AVI, and SI, were implemented using Geographical Information System techniques in Nea Moudania aquifer, Chalkidiki, Greece, to evaluate and identify groundwater vulnerability zones. The study area was classified into five categorie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 87 publications
1
6
0
Order By: Relevance
“…In many parts of the world, groundwater is the primary source of fresh water with 50% of portable water demands being met by groundwater, 40% of which is used for industry, and the remaining portion used for irrigation 6 . As the world's population grows, its dependence on groundwater also increases, with 33% of people depending on it to meet their daily needs 7 , 8 . Unfortunately, more groundwater is being consumed than replenished or recharged, which stresses on the availability of this precious natural resource.…”
Section: Introductionmentioning
confidence: 99%
“…In many parts of the world, groundwater is the primary source of fresh water with 50% of portable water demands being met by groundwater, 40% of which is used for industry, and the remaining portion used for irrigation 6 . As the world's population grows, its dependence on groundwater also increases, with 33% of people depending on it to meet their daily needs 7 , 8 . Unfortunately, more groundwater is being consumed than replenished or recharged, which stresses on the availability of this precious natural resource.…”
Section: Introductionmentioning
confidence: 99%
“…Many approaches have been developed to evaluate aquifer vulnerability. They include process-based methods, statistical methods, and overlay and index methods (Pouye et al, 2022;Kirlas et al, 2022;Eynakware et al 2022c and d;Kalinski et al (1993) and Eke (2017) opined that the basis of index-based integrated electrical conductivity is that the vertical travel time of water through a set of geological layers can be related to the resistivity properties of these layers, which implies that, the method (which is based on the principle that the distribution of electrical potential in the subsurface around current-carrying electrodes) depends on the electrical resistivity. Oli et al (2022) demonstrated that the protection degree of an aquifer or vulnerability may be considered directly proportional to the longitudinal conductance (LC) of the overburden materials.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the protective layers of the Earth safeguarding groundwater, the last few decades have witnessed a heightened risk to both the quality and quantity of groundwater. Various human activities, such as intensive agriculture, rapid urbanization, overexploitation, population growth, indiscriminate use of chemical fertilizers and pesticides, and unsustainable farming practices, have collectively contributed to the qualitative deterioration of groundwater (Green et al 2011;Saidi et al 2011;Kumar et al 2018;Kirlas et al 2022a;Taghavi et al 2022). The extensive use of chemical fertilizers and pesticides, in particular, has led to the degradation of groundwater quality and the pervasive issue of nitrate pollution in aquifers.…”
Section: Introductionmentioning
confidence: 99%
“…The choice of method depends on factors such as aquifer type, area scale, data availability and pollutant type (Etuk et al 2022). Given the expense and complexity of groundwater monitoring, (Jain, 2023), researchers have developed economical methodologies that are easier to apply and do not require extensive data or complex computations (Kumar et al 2015;Canora et al 2022;Kirlas et al 2022a). Notable groundwater vulnerability assessment methods include DRASTIC (Aller et al 1987), GOD (Foster, 1987), AVI (Van Stempvoort et al 1993), SINTACS (Civita 1994) and SI (Ribeiro, 2000).…”
Section: Introductionmentioning
confidence: 99%